2021
DOI: 10.1093/femsec/fiab062
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal diversity and community assembly: affected by island size or type?

Abstract: Fungi have a huge biodiversity and play important roles in soil biogeochemical cycling in island ecosystems. Although island biogeography has been widely studied for macroorganisms, fungal community assembly in true islands and its relationship with island area are less documented. We examined soil fungal communities in 18 oceanic islands of two types (eight non-coral islands and 10 coral islands) using the Illumina MiSeq sequencing technique. Our results showed that fungal α-diversity (species richness) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…We found that fungal community assembly was mainly driven by a deterministic process, rather than a stochastic process, across the three compartments of leaf, root, and soil. Similarly, previous studies demonstrated that soil fungal community assemblies were strongly shaped by deterministic (niche-based) factors (e.g., [ 40 , 41 ]). For root-associated fungal communities, deterministic processes dominated at most of the sites ( 42 ), while neutral processes still had a minor influence on community assembly and might be important in spatially isolated communities as well as those with strong gradients of fungal diversity ( 42 , 43 ).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We found that fungal community assembly was mainly driven by a deterministic process, rather than a stochastic process, across the three compartments of leaf, root, and soil. Similarly, previous studies demonstrated that soil fungal community assemblies were strongly shaped by deterministic (niche-based) factors (e.g., [ 40 , 41 ]). For root-associated fungal communities, deterministic processes dominated at most of the sites ( 42 ), while neutral processes still had a minor influence on community assembly and might be important in spatially isolated communities as well as those with strong gradients of fungal diversity ( 42 , 43 ).…”
Section: Discussionsupporting
confidence: 59%
“…A neutral community model, proposed by Sloan et al ( 76 ), was used to determine the contribution of stochastic processes to the fungal community assembly by predicting the relationship between the occurrence frequencies of OTUs (the proportion of local communities in which each OTU is detected) and their abundance (the mean relative abundance across all local communities) ( 41 , 76 ). This model emphasizes the effect of stochastic dispersal and drift but ignores the ecological differences between species and their responses to the surrounding environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, stochastic processes emphasize the role of probabilistic dispersal and ecological drift ( Hubbell, 2001 ; Vellend et al., 2014 ). In recent decades, an increasing number of studies indicated that deterministic and stochastic processes simultaneously drive fungal community assembly, but the relative importance of these two processes is dependent on scales and habitats type ( Schröter et al., 2019 ; Hussain et al., 2021 ; Zhang et al., 2021 ; Zheng et al., 2021 ). For example, soil fungal communities in the island were mainly governed by deterministic processes regardless of island type ( Zheng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coral are highly porous; the low trace-nutrients and waterretention properties do not favour plant growth [73]. While plant being a significant determinant for fungal diversity [11], this translates to lowered soil fungal diversity as reported in other oceanic coral islands [74]. Microbiome study of Taiwan's offshore island have highlighted the difference and important in soil type and the distinct microbiome structure observed between the Matsu archipelagos, GI and OI [33].…”
Section: Discussionmentioning
confidence: 99%